A Pragmatic Analysis Of Leech's Maxim Found In The Princess And The Frog Movie Script - Lestari, Puji, Drs. Agus Wijayanto, Ph.D, Drs. Sigit Haryanto, M.Hum (2013)
This study focused on Leech's maxim of politeness principle found in The Princess and the Frog movie script. This research aimed to explain the kinds of Leech's maxims which were observed and flouted by the characters in The Princess and the Frog movie script. Then, it also identified the speech act used by the characters in which the maxim were observed and flouted. The last, it classified the intention of speakers when they observed and flouted Leech's maxim. The research conducted on qualitative method. The data source was The Princess and the Frog movie script. The data were the utterances of the characters in The Princess and the Frog movie script. The data were collected using documentation. After collecting data, the data were classified into six maxims of politeness principle. Then, drawn conclusion based on the research finding. The results of study show that there were six maxims observed by the characters: tact maxim, generosity maxim, approbation maxim, modesty maxim, agreement maxim, and sympathy maxim. Then, there were three maxims flouted by the characters: tact maxim, generosity maxim and agreement maxim. The speech act involved in the maxim observant and flouts were assertive / representative, directive, commissive and expressive.